Primary Percutaneous Coronary Intervention of ST-segment Elevated Myocardial Infarction- Experiences in a Tertiary Care Hospital - Islam, AHM Waliul; Munwar, Shams; Reza, AQM; Bhuiyan, Azfar H; Ahmed, Tamzeed; Rahman, Kazi Atiqur; Ali, M Atahar; Alam, Shamsul; Rahman, Zia Ur; Yusuf, Intekhab; et al. (Cardiovascular Journal, 2022)
Background: Primary percutaneous coronary intervention (pPCI) is the preferred and established mode of treatment in ST elevated myocardial infarction (STEMI). Exact data on procedural outcome in patient undergoing primary PCI in our population is not well documented. We have carried out this study to see the prognosis, in-hospital, and 12-month survival outcome of our patients. Methods: Patients were enrolled in the observational non-randomized prospective cohort between November 2017-Mar 2020, who were presented into our emergency department with acute onset of severe chest pain or angina with ECG evidenced acute ST elevated myocardial infarction. Total 182 patient (Female 14; Male 168) were enrolled in this study. Results: Out of 182 patients, anterior MI were 47.8% (n=87) and inferior MI 50.5% (n=92) and lateral MI 1.6% (n=3). Presentation to ER from the onset of chest pain for female :123 min vs. male: 112 min and average door-to-balloon time were for female: 53 min vs. male: 50 min. Hospital admission of STEMI were more after 5 pm to next morning 9 am. Death were more in anterior STEMI than inferior STEMI. At presentation 10.4% (n=19) patents were in cardiogenic shock with STEMI, 42.1%(n=8) patients with anterior MI, 57.9% (n=11) in inferior MI group. Total, 15 (8.2%) patients died; 93.3% (n=14) within one week of primary PCI due to shock and poor LV function and subsequent development of LVF with arrhythmia and 6.7% (n=1) patient died 6 months after pPCI due to other cause. Conclusion: In this prospective observational cohort study, we found that PCI is a good and effective treatment modality in treating STEMI patient with better myocardial salvage and avoidance of life-threatening complications. Our procedural success rate is 91.8% and patients are doing well with regular follow up at our OPD 12-months after primary PCI. Cardiovasc j 2022; 14(2): 111-120